Fine meshwork : Philip Roth, Edna O'Brien, and Jewish-Irish literature - O'Brien, Dan (Irish studies., 2020)
"This study draws together for the first time the major authors, Edna O'Brien and Philip Roth, by tracing their long literary friendship and the striking parallels in their work and reception. In doing so, it considers them in both a national and a transnational context, and provides a novel means of understanding the interplay between Irish and Jewish-American literature"--